Robotics in Surgery: Enhancing Precision, Safety, and Patient Outcomes - Anggun Wida Prawira; Vindi Tyastutik (Journal of World Future Medicine, Health and Nursing, 2025)
Robotic-assisted surgery has revolutionized modern surgical practice by enhancing precision, reducing invasiveness, and improving patient outcomes. Traditional surgical techniques are often limited by human dexterity, fatigue, and the complexity of intricate procedures, which can increase the risk of complications and prolong recovery. Robotics offers advanced visualization, tremor filtration, and enhanced instrument control, enabling surgeons to perform complex procedures with greater accuracy and consistency. This study investigates the impact of robotic-assisted surgery on surgical precision, safety, and patient outcomes across multiple specialties. A systematic review and meta-analysis were conducted, synthesizing data from clinical trials, observational studies, and surgical outcome reports. Metrics analyzed included intraoperative precision, complication rates, operative time, postoperative recovery, and patient satisfaction. Results indicate that robotic surgery significantly reduces intraoperative errors, minimizes blood loss, shortens hospital stays, and enhances functional recovery compared to conventional techniques. Surgeons reported improved ergonomics and operative control, contributing to procedural consistency and reduced fatigue. The study concludes that robotics in surgery represents a critical advancement in surgical care, offering tangible benefits for both patients and clinicians. Successful integration requires continued training, technological refinement, and assessment of cost-effectiveness to ensure sustainable adoption. These findings support the expansion of robotic-assisted interventions as a standard of care in complex surgical procedures.